Comparative studies on the rhizosphere and rhizoplane mycoflora of tomato cv. ‘Pusa Ruby’ at planting and harvesting time - S.K. SAXENA, REKHA ARYA* and (Indian Phytopathology, 2009)
Studies were made to compare the associated rhizosphere mycoflora of tomato in two different growing seasons. Fungi were isolated from rhizosphere and rhizoplane of tomato c.v. Pusa Ruby at plantation and harvest time during two growing seasons i.e. March & September. Higher number of fungi was isolated in first growing season. Microbial activity was more at early stages of growth of plants. Deuteromycetes were the dominant group throughout the studies, saprophytic and antagonistic fungi were higher during harvest.